The effect of milling parameters on the mechanochemical synthesis of Pd–CeO2 methane oxidation catalysts. Issue 16 (15th July 2019) - Danielis, Maila; Colussi, Sara; de Leitenburg, Carla; Soler, Lluís; Llorca, Jordi; Trovarelli, Alessandro
Abstract : Pd–ceria interaction can be tuned by suitable milling intensity to obtain highly active methane oxidation catalysts. Abstract : The preparation of catalytic materials via mechanochemical routes is a very promising alternative to complex wet chemical syntheses due to its simplicity, versatility and ecological advantages. The mechanical mixing of Pd nanoparticles and CeO2 results in very active methane oxidation catalysts; here we explore the effect of milling parameters on the overall performance of Pd–ceria catalysts. The high methane combustion activity is the result of nanoscale interaction between palladium and cerium oxide and it is shown to be strongly dependent on the intensity of milling. This was investigated through methane combustion tests up to 1173 K and characterized by means of temperature programmed oxidation and reduction experiments. The morphological features of the obtained materials were investigated by HRTEM analysis and correlated to the catalytic behavior.